1965
DOI: 10.1063/1.1714596
|View full text |Cite|
|
Sign up to set email alerts
|

Volume Compressibility of BeO and Other II-VI Compounds

Abstract: The volume compressibilities of BeO, ZnS, CdS, CdSe, and CdTe have been measured to 45 kbar. Solidsolid transitions were observed in CdS, CdSe, and CdTe at 17.5, 21.3, and 31.8 kbar, respectively, with corresponding volume changes of 16.0%, 16.4%, and 16.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(31 citation statements)
references
References 17 publications
2
27
1
1
Order By: Relevance
“…The data from our measurements of the ultrasound velocity in samples of BeO of different shape and size (see Tables 1 -4) differed significantly from the calculated and experimental values of other investigators [10,11] (see Table 5). …”
Section: Velocity and Absorption Of Ultrasound In Beryllium Oxide Cercontrasting
confidence: 74%
“…The data from our measurements of the ultrasound velocity in samples of BeO of different shape and size (see Tables 1 -4) differed significantly from the calculated and experimental values of other investigators [10,11] (see Table 5). …”
Section: Velocity and Absorption Of Ultrasound In Beryllium Oxide Cercontrasting
confidence: 74%
“…Under low pressures p (<50 MPa), ÷ » a = 4.13´10 -12 Pa -1 . It can be seen that the discrepancy between the calculated and experimental [16] values is around 20%. Chang and Cohen [15] report the experimental value ÷ = 4.76´10 -12 Pa -1 , whose deviation from our calculation is~5%.…”
mentioning
confidence: 83%
“…According to available experimental data [16], the temperature dependence ÷ is described by the following equation:…”
mentioning
confidence: 99%
“…The high-pressure behavior of this compound has attracted continuous interest over the last three decades. In the early studies at room temperature, a phase transition was observed around 3.5 GPa, by optical absorption [1], electrical resistance [2], volume change [3,4] and X-ray diffraction [5 to 8] measurements. The highpressure phase was identified as having a rock-salt structure being stable up to a pressure of % 10 GPa [7 to 10].…”
Section: Introductionmentioning
confidence: 99%